(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: In the care of suffering the medical professionals need scientific knowledge, technical skill, moral understanding of profession and awareness about the relevant laws of the land. The present study was conducted to assess medico- legal awareness of practicing obstetricians and gynecologists. Materials & Method: The present study was conducted on 156 gynecologist. All were provided with standard questionnaire consisting of ten questions was given to them and their response was collected. Results: Age group 30-45 years had 30, 35-40 years had 45, 40-45 years had 50 and >45 years had 31 subjects. The difference was significant (P< 0.05). Questionnaire used was promptness in examination of victim of sexual assault, procedure related to Death Certification in MLCs, evidence Preservation in rape cases, awareness of Laws related to Obst.& Gynac Practice, real Causes of the Negligence Complaints, Awareness Regarding the provisions of PCPNDT Act and awareness about need of examining genuine MLCs. Most of the subjects was aware. The difference was significant (P< 0.05). Conclusion: Most of the gynecologist had sufficient awareness regarding medico- legal issues.